Mathematics Learning Using the Traditional Papuan Media Approach “Omtim (Sago Leaf Veins)” - Levi Pada lulu (Jurnal Ilmiah Mandala Education (JIME), 2026)
Learning mathematics may seem boring and difficult for some, but for many, it's a knowledge that can provide solutions and significantly assist people in achieving their dreams. For example, becoming proficient in mathematics can help others gradually develop a love for learning mathematics. Mathematics is a highly abstract subject, so it's true that some people are somewhat allergic and fearful of the word, as it seems to them a threat that disrupts their lives, with numbers and formulas that are so difficult to absorb. However, it's important to realize that understanding mathematics is actually quite fascinating, as it can be done through very simple and inexpensive tools. One such tool is "OMTIM," or "Sago Vein Leaf" in Indonesian.Sago Vein Leaf is a naturally occurring plant whose fruit is often used as a staple food by the people of Papua and surrounding areas. Sago fruit can be processed into a traditional Papuan dish called "PAPEDA." Research has shown that using sago leaf veins can help students understand number operations, including addition (+), subtraction (-), multiplication (*), and division (÷). The results indicate that using sago leaf veins makes it easier for students to understand and operate based on the rules, functions, and formulas of number operations.